Past, present and future of a meandering river in the Bolivian Amazon basin. Issue 4 (12th February 2021) - Arnez Ferrel, Kattia Rubi; Nelson, Jonathan Mark; Shimizu, Yasuyuki; Kyuka, Tomoko
Abstract: Field observations on small rivers of the Amazon basin are less common due to their remote location and difficult accessibility. Here we show, through remote sensing analysis and field works, the planform evolution and riverbed topography of a small river located in the upper foreland Amazon basin, the Ichilo River. By tracking planform changes over 30 years, we identified the factors that control meander migration rates in the Ichilo River: cutoffs, climate and human interventions. The data suggest that neck cutoffs are the main controls in the Ichilo River, with an annual density of 0.022 cutoffs/km. In addition, climate controls have been identified in the form of high‐precipitation events that may have promoted cutoffs, an increase in meander migration rate and channel widening. The width distribution of the Ichilo River is well represented by general extreme value and inverse Gaussian distributions. The spatiotemporal variability of meandering migration rates in the Ichilo River is analysed in two locations where neck cutoffs are expected. Analysing the distance across the neck in these two points, we predict the occurrence of a new cutoff. The combined methodology of bathymetric surveys and structure from motion photogrammetry shows us the Ichilo riverbed topography and banks at high resolution, where two scour holes were identified. Finally, we discuss the impact of planform changes of the Ichilo River on communities that are established along its riverbanks. Abstract : The planform dynamics and bed topography of the Ichilo River, a small meandering river in the Amazon basin, are studied through remote sensing analysis and field works. Bathymetric surveys and structure from motion photogrammetry were combined to obtain data of high resolution. Climate, cutoffs and anthropogenic activity were identified as main controls on meander migration rates of the Ichilo River.